2006
DOI: 10.1038/sj.cdd.4401866
|View full text |Cite
|
Sign up to set email alerts
|

Anti-idiotype-mediated epitope spreading and diminished phagocytosis by a human monoclonal antibody recognizing late-stage apoptotic cells

Abstract: Apoptotic cells are considered an important auto-antigenic source in diseases such as systemic lupus erythematosus (SLE). A human monoclonal antibody demonstrating exquisite specificity towards late-stage apoptotic cells was generated from an SLE patient. Polyreactive recognition of ribonucleoproteins Ro52 and Ro60 was observed. The antibody significantly diminished the phagocytosis of apoptotic cells and a concomitant decrease in transforming growth factor-b (TGF-b) secretion was observed. Light and heavy cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 39 publications
3
8
0
Order By: Relevance
“…Lupus appears to be characterized by excessive apoptosis as well as defective clearance of apoptotic debris, both of which would be expected to lead to the accumulation of self‐antigens and, possibly as a consequence, an enhanced susceptibility to autoimmune disease. The specific cell‐surface recognition of “late‐stage” apoptotic cells (as defined by the presence of apoptosis‐specific moieties along with demonstrated retention of plasma membrane integrity) by antibodies has been previously reported both by us 22, 23 and by other investigators 16, 24. In this study, the IgG and IgM apoptotic cell‐specific murine monoclonal antibodies generated demonstrated cross‐reactivity across several RNP autoantigens.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Lupus appears to be characterized by excessive apoptosis as well as defective clearance of apoptotic debris, both of which would be expected to lead to the accumulation of self‐antigens and, possibly as a consequence, an enhanced susceptibility to autoimmune disease. The specific cell‐surface recognition of “late‐stage” apoptotic cells (as defined by the presence of apoptosis‐specific moieties along with demonstrated retention of plasma membrane integrity) by antibodies has been previously reported both by us 22, 23 and by other investigators 16, 24. In this study, the IgG and IgM apoptotic cell‐specific murine monoclonal antibodies generated demonstrated cross‐reactivity across several RNP autoantigens.…”
Section: Discussionsupporting
confidence: 65%
“…IgM antibodies against low‐density lipoproteins on apoptotic cells can inhibit phagocytosis of apoptotic cells 33, as can an IgM antibody derived from animals immunized with dying cells 34. Such studies and others 23, 35, 36 question whether, in all cases, the uptake of apoptotic cells is strictly PS‐dependent or whether other moieties on dying cells may also contribute. Antibodies such as IgM 2C11, which binds LPC as well as apoptotic blebs (also shown to act as chemo‐attractants for phagocytes) and can also efficiently prevent the phagocytic uptake of apoptotic cells, could be envisaged to be powerful disease perpetuators in an environment rendered pro‐inflammatory, due to bacterial infection, for example.…”
Section: Discussionmentioning
confidence: 99%
“…Gandhi and colleagues report that a human monoclonal antibody polyreactive with Ro52 and Ro60, which bound late-stage apoptotic but not healthy MOLT-4 cells, significantly diminished the phagocytosis of these cells by activated THP-1 cells (39). Since the antibody employed was IgM, this would explain the absence of uptake via Fc receptor as reported in our previous studies of maternal IgG anti-Ro/La-opsonized apoptotic cardiocytes cocultured with macrophages (40).…”
Section: Al That Mammary Epithelial Cells Absent Classic Fc Receptormentioning
confidence: 69%
“…Anti-dsDNA autoantibody, which is a serological hallmark of SLE, has been proved to be pathogenic and could cause subsequent tissue deposition of immune complexes (ICs) and tissue damage (3,4). A series of events including polyclonal B lymphocyte activation, molecular mimicry, and disruption of an idiotypic network have been reported to be involved in the process of autoantibody production during the pathogenic development of the disease (5)(6)(7)(8). Genetic studies in SLE patients showed that anti-dsDNA autoantibodies, which generally belong to IgG subtype with high-affinity binding to dsDNA, differ from the germline because of somatic mutations (9).…”
mentioning
confidence: 99%